STUDY OF CORROSION BEHAVIOUR OF C 26000 BRASS IN SOLUTIONS CONTAINING CHLORIDE IONS AT ROOM TEMPERATURE - (NIM 221 92 017), Rukiah
Abstract : Brass alloy (C 26000) containing zink 30 % is susceptible to dezincification. Since zinc metal is much more active than copper metal, zinc dissolves and leaves porous copper metal during dezincification of the alloy. This form of corrosion can occurs at both outside and inside crevices. The dezincification og the alloy can occur especially in solutions containing chloride with other oxidizing ions, in stagnant solution and at low pH. Study of such corrosion behaviour of the alloy in chloride containing solution was done by observing its corrosion potential versus time, measuring its corrosion rate (using polarization resistance method) and examining its metallographic structure. The electrochemical measurements were carried out in aquatic solution containing various NaCI, FeCl3 and CuC12 concentrations and pH. Dezincification mechanisms occuring respectively at potential + 0.1 V, - 0, IV and -0.05V (vs SHE) were also discussed. Simultaneous dissolution of copper and zinc occured at potential ranged from -0.03 V to + 0.20 V (vs SHE), while redeposition of copper was likely to occur whenever the concentration of copper ion at the alloy surface was high enough. Addition of CuCl2 or FeCl3 into the test solutions resulted in increasing their corrosion rate due to the increase of reduction reaction rate. On the other hand, the rate of kuningan dezincification increased by increasing chloride concentration in acidified solution or by decreasing pH at constant chloride concentration.